INTERRELATION DEGREE OF SEVERITY PTERYGOPALATINE GANGLIONITIS WITH THE HYGIENIC CONDITION OF THE ORAL CAVITY - I.A. Kolisnyk (Український стоматологічний альманах, 2018)
Pterygopalatine ganglionitis is the most often among pathological syndromes of the face. Polymorphism of its manifestations significantly complicates diagnosis and choice of the optimal method of treatment, due to topographic, anatomical and functional features of the structure of peripheral vegetative nervous system of the head.